Dasatinib Dose Optimization Based on Therapeutic Drug Monitoring in Patients with Chronic-Phase Chronic Myeloid Leukemia - Cheng F; Cui Z; Li Q; Wang L; Zhang Y; Li W (Drug Design, Development and Therapy)
Fang Cheng,1,2 Zheng Cui,1,2 Qiang Li,1,2 Liu Wang,1,2 Yu Zhang,1,2 Weiming Li3 1Department of Pharmacy, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People’s Republic of China; 2Hubei Province Clinical Research Center for Precision Medicine for Critical Illness, Wuhan, 430022, People’s Republic of China; 3Department of Hematology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People’s Republic of ChinaCorrespondence: Yu Zhang, Email zhangwkp@163.com Weiming Li, Email lee937@126.comBackground: Although a dosage decrease regimen for chronic phase chronic myeloid leukemia (CML-CP) has been suggested, there is a marked lack of guidance on individualizing medication dosages for patients.Methods: Our aim was to explore the application of therapeutic drug monitoring (TDM) as a strategy for optimizing dasatinib dosage in patients with CML-CP.Results: It was observed that patients administered a dosage of 100 mg exhibited significantly higher concentrations than those given 50 mg, with no marked difference in concentration between branded and generic drugs. Further analysis unveiled a robust correlation between peak concentration (Cmax) and clinical response (major molecular response (MMR): 103.8 ± 54.0 ng/mL versus 48.6 ± 13.9 ng/mL, P < 0.001; deep molecular response (DMR): 112.7 ± 57.6 ng/mL versus 66.2 ± 36.1 ng/mL, P = 0.001). Patients with a Cmax > 51.85ng/mL were more likely to achieve MMR, while those with a Cmax surpassing 112.5 ng/mL had a higher probability of attaining DMR. We successfully implemented dasatinib dose reduction based on concentrations without loss of DMR in 22 patients undergoing first-line therapy. Moreover, trough concentrations (Cmin) > 2.48 ng/mL were closely associated with the onset of pleural effusion. Older patients demonstrated higher Cmin and Cmax, irrespective of whether they were on a 50 mg or 100 mg dosage regimen.Conclusion: TDM-based dose optimization could lead to beneficial clinical outcomes for patients with CML-CP. Furthermore, in terms of blood drug concentration, our findings supply additional evidence supporting the first-line treatment regimen of 50 mg daily. Keywords: chronic myeloid leukemia, dasatinib, dose optimization, therapeutic drug monitoring, clinical response